2011
DOI: 10.1016/j.vetmic.2011.02.050
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity and associated pathology of Pasteurella multocida isolated from porcine pneumonia

Abstract: Pasteurella multocida is a widespread respiratory pathogen in pigs associated with atrophic rhinitis and contributing to aggravation of the pulmonary lesions. The aims of the present study were to characterize isolates of P. multocida from porcine bronchopneumonia by pulsed-field gel electrophoresis (PFGE), PCR based capsular typing and multilocus sequence typing (MLST) and to compare clonal complexes outlined with the type of histological lung lesions to investigate if a correlation between clonal lineages an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
21
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 34 publications
4
21
1
1
Order By: Relevance
“…Cluster V contained isolates from two complexes, ST13 from Sorriso and ST74 from Campo Grande. Most of the isolates from this study belong to ST74 and ST13, which was similar to swine in Norway (PORS et al, 2011), except that ST50 was absent in our study. These isolates are probably species-specific (HOTCHKISS et al, 2011) with the exception of ST13, which has also been identified in cattle.…”
Section: Resultssupporting
confidence: 50%
“…Cluster V contained isolates from two complexes, ST13 from Sorriso and ST74 from Campo Grande. Most of the isolates from this study belong to ST74 and ST13, which was similar to swine in Norway (PORS et al, 2011), except that ST50 was absent in our study. These isolates are probably species-specific (HOTCHKISS et al, 2011) with the exception of ST13, which has also been identified in cattle.…”
Section: Resultssupporting
confidence: 50%
“…Porém, o número de amostras analisadas foi baixo, o que deve ser considerado na interpretação deste achado. Esse resultado pode ser explicado pela alta variabilidade antigênica entre as amostras de P. multocida isoladas de suínos (Pors, et al, 2011;Bethe et al, 2009).…”
Section: Discussionunclassified
“…Choi et al (15) report a prevalence of coinfection with PRRS and P. multocida to be 10.4%, PRRS and M. hyopneumoniae of 7% and PRRS and A. pneumoniae to be 6.2%. Also, the mixed infections have been described in several studies (16,17,18,19). In these studie,s the more common mixed infections were P. multocida with viruses or bacterial agents.…”
Section: Discussionmentioning
confidence: 94%